Combined isobutyryl‐CoA and multiple acyl‐CoA dehydrogenase deficiency in a boy with altered riboflavin homeostasis. Issue 4 (7th May 2022) - Tummolo, Albina; Leone, Piero; Tolomeo, Maria; Solito, Rita; Mattiuzzo, Matteo; Lepri, Francesca Romana; Lorè, Tania; Cardinali, Roberta; De Giovanni, Donatella; Simonetti, Simonetta; Barile, Maria
Abstract: In this report, we describe the case of an 11‐year‐old boy, who came to our attention for myalgia and muscle weakness, associated with inappetence and vomiting. Hypertransaminasemia was also noted, with ultrasound evidence of hepatomegaly. Biochemical investigations revealed acylcarnitine and organic acid profiles resembling those seen in MADD, that is, multiple acyl‐CoA dehydrogenase deficiencies (OMIM #231680) a rare inherited disorder of fatty acids, amino acids, and choline metabolism. The patient carried a single pathogenetic variant in the ETFDH gene (c.524G>A, p.Arg175His) and no pathogenetic variant in the riboflavin (Rf) homeostasis related genes ( SLC52A1, SLC52A2, SLC52A3, SLC25A32, FLAD1 ). Instead, compound heterozygosity was found in the ACAD8 gene (c.512C>G, p.Ser171Cys; c.822C>A, p.Asn274Lys), coding for isobutyryl‐CoA dehydrogenase (IBD), whose pathogenic variants are associated to IBD deficiency (OMIM #611283), a rare autosomal recessive disorder of valine catabolism. The c.822C>A was never previously described in a patient. Subsequent further analyses of Rf homeostasis showed reduced levels of flavins in plasma and altered FAD‐dependent enzymatic activities in erythrocytes, as well as a significant reduction in the level of the plasma membrane Rf transporter 2 in erythrocytes. The observed Rf/flavin scarcity in this patient, possibly associated with a decreased ETF:QO efficiency might be responsible for the observed MADD‐like phenotype. The patient's clinical picture improved after supplementation of Rf, l ‐carnitine, Coenzyme Q10, and also 3OH‐butyrate. This report demonstrates that, even in the absence of genetic defects in genes involved in Rf homeostasis, further targeted molecular analysis may reveal secondary and possibly treatable biochemical alterations in this pattern.